2015
DOI: 10.4103/0972-2327.165469
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoanatomical correlation in stroke related aphasia

Abstract: Context:With advances in neuroimaging, traditional views regarding the clinicoanatomic correlation in stroke patients with aphasia are being challenged and it has been observed that lesions at a given cortical or subcortical site may manifest with different aphasia profiles.Aims:To study as to whether there is a strict clinicoanatomical correlation between the type of aphasia and lesion site in patients with first ever stroke.Settings and Design:Observational study, based in a tertiary care center.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 16 publications
1
5
0
5
Order By: Relevance
“…Both conductive and nominal aphasia were uncommon and were found in only 8.3% and 2.8% respectively. Our results are similar to many other studies which found that both global and motor aphasia are the major subtypes [30,[37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…Both conductive and nominal aphasia were uncommon and were found in only 8.3% and 2.8% respectively. Our results are similar to many other studies which found that both global and motor aphasia are the major subtypes [30,[37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…5 Penelitian menunjukkan angka kejadian afasia pada stroke yang cukup tinggi, yaitu 13-40%. [6][7][8] Pemulihan afasia dapat terjadi secara bertahap dalam beberapa bulan pertama pascastroke. Menurut Watilla dkk pemulihan afasia sulit diprediksi karena banyak faktor yang memengaruhi proses pemulihan tersebut.…”
Section: Pendahuluanunclassified
“…Beberapa penelitian afasia menunjukkan tidak terdapat perbedaan insidens afasia antara jenis kelamin. 6,13 Kardioemboli merupakan penyebab terbanyak afasia pada stroke iskemik dalam penelitian ini. Hal ini terjadi karena emboli otak yang bersumber dari jantung sering kali berukuran besar, sehingga dapat menyebabkan gejala stroke lebih berat.…”
Section: Pembahasanunclassified
See 2 more Smart Citations